Combined Sliding Mode Control with a Feedback Linearization for Speed Control of Induction Motor - Ahmed, Aamir Hashim Obeid; Ajangnay, Martino O.; Mohamed, Shamboul A.; Dunnigan, Matthew W. (Iraqi Journal for Electrical and Electronic Engineering, 2011)
Induction Motor (IM) speed control is an area of research that has been in prominence for some time now. In this paper, a nonlinear controller is presented for IM drives. The nonlinear controller is designed based on input-output feedback linearization control technique, combined with sliding mode control (SMC) to obtain a robust, fast and precise control of IM speed. The input-output feedback linearization control decouples the flux control from the speed control and makes the synthesis of linear controllers possible. To validate the performances of the proposed control scheme, we provided a series of simulation results and a comparative study between the performances of the proposed control strategy and those of the feedback linearization control (FLC) schemes. Simulation results show that the proposed control strategy scheme shows better performance than the FLC strategy in the face of system parameters variation.